Development Of 3-D Optimized Perimeter Arrays For Near Surface Geophysical Survey Using Modified Compare-R Method - Fathi, Mohammed Saeed Abdullah
In earth resistivity imaging, the field data acquisition and the electrodes arrangement are significant aspects to consider for ensuring the highest data quality and highest model resolution. There are many conventional arrays with different geometries used for resistivity surveys and each of them has different performances. Recently, there is a new trend in resistivity data acquisition, which is optimized arrays that developed to improve the subsurface model resolution. This research focused on applying, improving and evaluating the optimized arrays based on a modified compare R method for 2-D resistivity surveys and its modification for the special case of 3-D resistivity surveys (constrained areas). In the 2-D resistivity surveys, the effectiveness and performance of the noise-weighted compare R (NWCR) and compare R (CR) optimized arrays were evaluated in terms of improving the subsurface model resolution and detectability of the near surface targets. The effectiveness of these optimized arrays was compared with commonly used conventional arrays, namely Dipole-Dipole (DD), Wenner-Schlumberger (WS) and Wenner (W). This is demonstrated in three different stages containing synthetic model tests, laboratory experiment and field cases studies. The results show that both optimized arrays perform better resolution and better detectability of the near surface targets especially in the deepest part of the inversion images than conventional arrays. However, there is a slight improvement of NWCR in terms of lower data misfit and better targets detectability than other arrays.